The human right to water and its implementation through citizens’ initiatives and action - Nikolakakou (Ευαγγελία Νικολακάκου) Evangelia (Bioethica, 2019)
Whether there is a human right to water theoretically or in a normative context and whether such a right when legislatively established and protected via International Treaties and the National Law of States has practical application, constitutes one of the important topics of public discourse in environmental bioethics and more specifically in environmental justice. Citizens’ groups, trade unions and various social movements strongly support such a right, which can improve – without exception - the quality of life and enhance the well-being of everyone, regarding water issues. At a time when Europe promotes the privatization of public social services, the need for managing such issues through a rights-based approach becomes more and more urgent. Aligned with this need is the European Citizens’ Initiative (ECI) whose action aims to ensure affordable, safe and accessible water to all, through legislative proposals to the European Commission. In this essay, we will make an effort to examine whether the European Citizens’ Initiative met its set objectives regarding the implementation of the human right to water in the EU legislation and whether the European Commission has responded adequately to its demands.